Exploring Black adolescents’ perceptions of God during COVID-19: God images as a source of wellness - Parker, Janise S. (Mental health, religion & culture, 2022)
The purpose of this study was to examine challenges Black adolescents may experience because of COVID-19 and coping strategies employed to navigate their reported difficulties. The current study used secondary data analysis to understand how Black U.S. adolescents’ positive images of God contributed to their emotional well-being in response to stressors associated with COVID-19. Data from a larger study were extracted from 11 Black adolescents’ (Ages 12–17; 54.5% female) individual interview transcripts; and the research team used an interpretative phenomenology process to analyze the data. Participants’ experiences of God as a (a) Teacher, (b) Powerful Being, and (c) Comforter served as robust contributors to their feelings of strength, hope, assurance, calmness, contentment, and motivation, despite the challenges they encountered. This study presents a culturally responsive approach to understanding and potentially responding to Black adolescents’ mental health needs during the COVID-era.